2020
DOI: 10.24189/ncr.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather conditions on seasonal development, population structure and reproductive success on Dactylorhiza traunsteineri (Orchidaceae) in the Komi Republic (Russia)

Abstract: Due to specific biological features, high ornamental value and low resistance to anthropogenic factors, Orchidaceae species belong to the most vulnerable plants. To successfully protect their populations, comprehensive investigations of orchid biology and ecology are necessary. Long-term population studies are the most valuable. The paper presents data of population studies of Dactylorhiza traunsteineri, an orchid species listed in the Red Data Book of the Russian Federation. The field investigations have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Our analyses reveal consistent interactive effects of habitat, dormant season burning, and climatic variation on flowering, reproduction, and survival of Platanthera leucophaea . This work reinforces other North American [ 8 , 10 , 11 ] and European [ 7 , 9 ] studies that have found multi-year climatic effects on demographic processes in orchids. Our work also reinforces the positive effects of burning on maintaining tallgrass prairie.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analyses reveal consistent interactive effects of habitat, dormant season burning, and climatic variation on flowering, reproduction, and survival of Platanthera leucophaea . This work reinforces other North American [ 8 , 10 , 11 ] and European [ 7 , 9 ] studies that have found multi-year climatic effects on demographic processes in orchids. Our work also reinforces the positive effects of burning on maintaining tallgrass prairie.…”
Section: Discussionsupporting
confidence: 89%
“…ex Rchb.) Soo in northern Europe [ 9 ]. In the U.S. and Canada, precipitation thresholds during different phenological stages affect the flowering and reproduction processes of Platanthera praeclara Sheviak and Bowles [ 10 , 11 ] and the closely related Platanthera leucophaea [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest number of population-based studies has been concerned investigations of 1-2 orchid species (e.g. Raventós et al, 2015;Khapugin et al, 2016Khapugin et al, , 2017aBr-zosko et al, 2017;Puchnina, 2017;Kirillova & Kirillov, 2020). However, there are a few studies (Pierce et al, 2006;Stefaniak et al, 2013;Talalaj et al, 2017) concerning a higher number of orchid species which are more valuable for further comparison.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Russian Federation (Komijsko) states that the size of the orchid population is influenced by the climatic conditions of the current, as well as the previous growing season. The population is positively affected by the correlation of temperature and humidity [ 18 ]. In the territory of the Western Carpathians, orchids are hemisciophytes to sciophytes, which bind mainly to moderately warm habitats in lower positions.…”
Section: Introductionmentioning
confidence: 99%